2017
DOI: 10.1016/j.stemcr.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sirtuin Deacetylase Activity in LRRK2 G2019S iPSC-Derived Dopaminergic Neurons

Abstract: SummaryMitochondrial changes have long been implicated in the pathogenesis of Parkinson's disease (PD). The glycine to serine mutation (G2019S) in leucine-rich repeat kinase 2 (LRRK2) is the most common genetic cause for PD and has been shown to impair mitochondrial function and morphology in multiple model systems. We analyzed mitochondrial function in LRRK2 G2019S induced pluripotent stem cell (iPSC)-derived neurons to determine whether the G2019S mutation elicits similar mitochondrial deficits among central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 74 publications
9
89
0
Order By: Relevance
“…The authors found increased expression of sirtuins, a family of nicotinamide adenine dinucleotide (NAD) + ‐dependent protein deacetylases involved in mitochondrial metabolism, but a decrease in deacetylase activity and complex III levels. LRRK2 kinase inhibitor treatment was not sufficient to normalize levels of sirtuins in LRRK2 G2019S mesDA neurons (Schwab et al., ). Interestingly, the authors could not observe these phenotypes in iPSC‐derived peripheral neurons, indicating neuronal subtype‐specific susceptibility.…”
Section: Pd‐associated Lrrk2 Variants In Ipsc‐based Disease Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found increased expression of sirtuins, a family of nicotinamide adenine dinucleotide (NAD) + ‐dependent protein deacetylases involved in mitochondrial metabolism, but a decrease in deacetylase activity and complex III levels. LRRK2 kinase inhibitor treatment was not sufficient to normalize levels of sirtuins in LRRK2 G2019S mesDA neurons (Schwab et al., ). Interestingly, the authors could not observe these phenotypes in iPSC‐derived peripheral neurons, indicating neuronal subtype‐specific susceptibility.…”
Section: Pd‐associated Lrrk2 Variants In Ipsc‐based Disease Modelingmentioning
confidence: 99%
“…Interestingly, the authors could not observe these phenotypes in iPSC‐derived peripheral neurons, indicating neuronal subtype‐specific susceptibility. Moreover, LRRK2 G2019S neurons were shown to display decreased ATP content (Schwab et al., ; Su & Qi, ), accompanied by a decrease in mitochondrial membrane potential (Hsieh et al., ; Su & Qi, ). Both findings were also observed in other PD models in SNCA trp and mutant OPA1 neural progenitor cells (NPCs) (Flierl et al., ; Iannielli et al., ).…”
Section: Pd‐associated Lrrk2 Variants In Ipsc‐based Disease Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that there is an increase in SNCA transcription in LRRK2‐G2019S mutant neurons (Nguyen et al., ) but other groups showed no upregulation of SNCA (Reinhardt et al., 2013; Sanchez‐Danes et al., ). It has been reported that dopaminergic neurons derived from LRRK2 G2019S IPSCs showed abnormal mitochondrial trafficking and distribution(Schwab et al., ). This correlated to reduced activity of sirtuin deacetylase and low levels of nicotinamide adenine dinucleotide but sirtuin levels were high.…”
Section: Ipsc Models From Genetic and Sporadic Forms Of Pdmentioning
confidence: 99%
“…An increase in bidirectional mobility of mitochondria in neurons from LRRK2 G2019S PD patients was also reported as compared to neurons derived from healthy controls (Cooper et al., ). It has been reported that dopaminergic neurons derived from LRRK2 G2019S IPSC demonstrate abnormal mitochondrial trafficking and distribution(Schwab et al., ). This correlated to reduced activity of sirtuin deacetylase and low levels of nicotinamide adenine dinucleotide but sirtuin levels were high.…”
Section: Evidence For Mitochondrial Dysfunction In Ipsc Models Of Pdmentioning
confidence: 99%